Prevalence of antibodies to bluetongue virus and Anaplasma marginale in Montana yearling in Montana yearling cattle entering Alberta feedlots: Fall 2001 - Van Donkersgoed, Joyce (Canadian Veterinary Medical Association, 2004)
A serologic survey was conducted in yearling cattle imported into Alberta feedlots from Montana during October 2001 to estimate the prevalence of antibodies to bluetongue virus (BTV) and Anaplasma marginale in Montana yearling cattle. The apparent prevalence of antibodies to BTV when the competitive enzyme-linked immunosorbent assay (cELISA) was used was 0.37% (21/5608). Test positive cELISA samples were also all positive when tested by virus neutralization (VN) and they reacted to 1 or more BTV serotypes, including 2, 10, 11, 13, and 17. The apparent prevalence of antibodies to A. marginale when a recombinant cELISA (rcELISA) was used with a positive cutoff at 30% inhibition was 1.93% (108/5608). When the rcELISA positive cutoff was at 42% inhibition, the apparent prevalence was 0.73% (41/5608). After the reported sensitivity and specificity of the test had been accounted for, the A. marginale antibody results were consistent with a population that was either free of exposure or had a very low prevalence for A. marginale.